Characteristics of quantitative perfusion parameters on dynamic contrast‐enhanced MRI in mammographically occult breast cancer. (8th September 2016) - Ryu, Jung Kyu; Rhee, Sun Jung; Song, Jeong Yoon; Cho, Soo Hyun; Jahng, Geon‐Ho
Abstract : The purpose of this study was to compare the characteristics of quantitative perfusion parameters obtained from dynamic contrast‐enhanced (DCE) magnetic resonance imaging (MRI) in patients with mammographically occult (MO) breast cancers and those with mammographically visible (MV) breast cancers. Quantitative parameters (AUC, K trans, k ep, v e, v p, and w i ) from 13 MO breast cancers and 16 MV breast cancers were mapped after the DCE‐MRI data were acquired. Various prognostic factors, including axillary nodal status, estrogen receptor (ER), progesterone receptor (PR), Ki‐67, p53, E‐cadherin, and human epidermal growth factor receptor 2 (HER2) were obtained in each group. Fisher's exact test was used to compare any differences of the various prognostic factors between the two groups. The Mann‐Whitney U test was applied to compare the quantitative parameters between these two groups. Finally, Spearman's correlation was used to investigate the relationships between perfusion indices and four factors — age, tumor size, Ki‐67, and p53 — for each group. Although age, tumor size, and the prognostic factors were not statistically different between the two groups, the mean values of the quantitative parameters, except w i in the MV group, were higher than those in the MO group without statistical significance ( p = 0.219 ) . The k ep value was significantly different between the two groups ( p = 0.048 ), but the other parameters were not. In the MO group, v p with size, v e with p53, and K trans and v p with Ki‐67 had significant correlations ( p < 0.05 ). However, in the MV group, only k ep showed significant correlation with age. The k ep value was only the perfusion parameter of statistical significance between MO and MV breast cancers. PACS number(s): 87.19.U‐, 87.61.‐c